Akuntabilitas Pelayanan Publik di Desa Administratif Kildor Kecamatan Kesuy Watubela Kabupaten Seram Bagian Timur - Rumada, Walena; Pieter Sammy Soselisa; Waisapy, Jeanly (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to examine the accountability of public services in Kildor Administrative Village, Kesuy Watubela District, East Seram Regency. The research uses a qualitative approach, with a total of 10 informants selected through purposive sampling. Data collection techniques include observation, interviews, and documentation. The findings indicate that public service accountability in Kildor Administrative Village has been implemented effectively, analyzing and describing the service process as well as the supporting and inhibiting factors. The supporting factors include the enthusiasm and mutual encouragement among employees, conducting coordination meetings or evaluations, and fostering awareness of serving the community with sincerity and integrity. On the other hand, the inhibiting factors involve the lack of human resources and inadequate infrastructure and facilities.